Haemodynamic effects of glyceryl trinitrate during continuous 24 hour infusion in patients with heart failure. Issue 2 (August 1994) - Ghio, S; Poli, A; Ferrario, M; Campana, C; Diotallevi, P; Eleuteri, E; Mussini, A; Specchia, G; Montemartini, C
Abstract : OBJECTIVE–To investigate whether the susceptibility to tolerance to glyceryl trinitrate is similar in different vascular beds in patients with chronic heart failure. PATIENTS–Twenty patients with heart failure underwent a continuous infusion of glyceryl trinitrate over 24 hours followed by administration of N-acetylcysteine (5 g intravenously) in a bolus. MAIN OUTCOME MEASURES–Haemodynamic measurements under control conditions, at peak titration of glyceryl trinitrate at 24 hours, and after N-acetylcysteine; plasma renin activity and packed cell volume. RESULTS–After 24 hours of infusion the acute reduction in right atrial pressure had largely waned, while pulmonary vascular resistance remained improved and systemic resistance, which was not reduced at peak titration, significantly decreased with respect to control conditions. The effects of N-acetylcysteine and hormonal responses were different in patients who did and did not develop tolerance to glyceryl trinitrate. CONCLUSIONS–The haemodynamic profile of glyceryl trinitrate changed substantially during the study from a predominantly venodilator action at peak titration to a predominantly arteriolar dilatation after 24 hours of infusion. The different effects of N-acetylcysteine and the different hormonal responses confirm the multifactorial pathogenesis of tolerance to glyceryl trinitrate.